2019
DOI: 10.3892/mmr.2019.10229
|View full text |Cite
|
Sign up to set email alerts
|

ILF3 promotes gastric cancer proliferation and may be used as a prognostic marker

Abstract: Interleukin enhancer-binding factor 3 (ILF3) may function as a transcriptional coactivator and has been reported to be involved in tumor proliferation and metastasis; however, its role and clinical value in gastric cancer (GC) remains unclear. To understand the value of ILF3 in GC, a total of 80 matched samples selected from GC tissues and the adjacent mucosa were used to evaluate the expression of ILF3 and its association with clinical characteristics. Furthermore, its biological functions and mechanisms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Thus, our data strongly demonstrate a direct interaction between ELDR and ILF3. ILF3 is a nucleotide-binding protein, functions as a transcriptional activator, and regulates the mRNA synthesis of target genes, mRNA stability, primary miRNA processing, translation resulting induction in tumor proliferation, invasion, angiogenesis, and metastasis (Jia et al, 2019;Liu et al, 2019). We examined the consequence of ELDR and ILF3 interaction in ELDR-depleted OSCC by Western blot analysis.…”
Section: Eldr Interacts With Ilf3mentioning
confidence: 99%
“…Thus, our data strongly demonstrate a direct interaction between ELDR and ILF3. ILF3 is a nucleotide-binding protein, functions as a transcriptional activator, and regulates the mRNA synthesis of target genes, mRNA stability, primary miRNA processing, translation resulting induction in tumor proliferation, invasion, angiogenesis, and metastasis (Jia et al, 2019;Liu et al, 2019). We examined the consequence of ELDR and ILF3 interaction in ELDR-depleted OSCC by Western blot analysis.…”
Section: Eldr Interacts With Ilf3mentioning
confidence: 99%
“…Accumulating evidence has shown that ILF3 is abnormally expressed in a series of malignancies, and is involved in tumor proliferation, metastasis, and invasion ( Hu et al, 2013 ; Jiang et al, 2015 ; Liu et al, 2019 ). However, the action and consequence of ILF3 in ESCC are not well elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The ILF2/ILF3 complex has been reported to participate in multiple cellular processes such as DNA repair and replication ( Shamanna et al, 2011 ), mRNA stabilization ( Jiang et al, 2015 ), transcription ( Tsai et al, 2021 ), translation inhibition ( Nourreddine et al, 2020 ), and micro-RNA biogenesis ( Todaka et al, 2015 ; Higuchi et al, 2016 ). Recently, the role of ILF2 and ILF3 in tumors is emerging, and it has been found that they were involved in the occurrence and development of various types of malignancy, including gastric cancer ( Yin et al, 2017 ; Liu et al, 2019 ), non–small-cell lung cancer ( Ni T. et al, 2015 ; Cheng et al, 2018 ), breast cancer ( Hu et al, 2013 ; Jin et al, 2018 ), and pancreatic carcinoma ( Wan et al, 2015 ; Li et al, 2019 ). Additionally, ILF2 has been reported to be highly expressed in ESCC and suggested to be a prognostic factor for the poor outcome of ESCC patients ( Ni S. et al, 2015 ; Wen-Jian et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…ILF3 may function as a transcriptional coactivator, and regulates tumor proliferation and metastasis. ILF3 results in the deterioration of GC by promoting the proliferation of GC cells, and the detection of this protein may be useful in the prognostic prediction of GC patients (39). However, its role in the drug resistance of GC patients remains unclear.…”
Section: A B C Dmentioning
confidence: 99%